2017
DOI: 10.1111/anu.12582
|View full text |Cite
|
Sign up to set email alerts
|

The effects on some non-enzymatic antioxidants and oxidative stress ofAstacus leptodactylus(Esch., 1823) of starvation periods

Abstract: This study investigated the effect of starvation (78 days) and refeeding (33 days) on the oxidative stress [malondialdehyde (MDA)] and the non‐enzymatic antioxidants [vitamin E (VE), vitamin C (VC), vitamin A (VA), beta carotene (βC) and reduced glutathione (GSH)] in the hepatopancreas, muscle and gill tissues of freshwater crayfish (Astacus leptodactylus). Crayfish were divided into three experimental groups: control (fed), starved (not fed) crayfish for 78 days and refeeding crayfish for 33 days after 78 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…This decrease may be due to the intensification of turnover between reduced and oxidized glutathione under stress conditions and as a result caused an increase in the consumption of some peptides for the synthesis of heavy metalbinding proteins like metallothioneins (Radwan et al, 2010). In this regard, Barim (2018) found that GSH was significantly decreased in the hepatopancreas of freshwater crayfish (Astacus leptodactylus) upon starvation. They attributed this decrease in GSH content during exposure to starvation to an increased utilization of GSH, which can be converted into oxidized glutathione, and inefficient GSH regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease may be due to the intensification of turnover between reduced and oxidized glutathione under stress conditions and as a result caused an increase in the consumption of some peptides for the synthesis of heavy metalbinding proteins like metallothioneins (Radwan et al, 2010). In this regard, Barim (2018) found that GSH was significantly decreased in the hepatopancreas of freshwater crayfish (Astacus leptodactylus) upon starvation. They attributed this decrease in GSH content during exposure to starvation to an increased utilization of GSH, which can be converted into oxidized glutathione, and inefficient GSH regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] . Moreover, in 2017, from the basal strain, three additional populations were generated, which differed in terms of the Cd concentration in the food (11,22 and 44 μg of Cd per g of food (dry weight)) 29 . Prior to the present experiment, approximately 20 generations of Cd-selected insects had occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy enables the maintenance of homeostasis during winter dormancy, which is associated with food and energy deficiency, because autophagy supplies cells with nutrients 7 . Starvation is considered to cause prooxidative changes 8 11 , generating endoplasmic reticulum (ER) stress, which is recognized as a proautophagic factor 12 , 13 . The same mechanisms explain the proautophagic action of metals such as cadmium 14 .…”
Section: Introductionmentioning
confidence: 99%
“…avoiding excessive lipid accumulation; Grigorakis & Alexis, ) for processing purposes. It has been shown that starvation can induce depletion of organ antioxidant stores and increase the generation of oxygen free radicals, particularly in liver (Barim‐Öz, ; Bayir et al, ; Furné et al, ; Morales, Pérez‐Jiménez, Carmen Hidalgo, Abellán, & Cardenete, ; Pascual, Pedrajas, Toribio, López‐Barea, & Peinado, ; Pérez‐Jiménez, Guedes, Morales, & Oliva‐Teles, ). In addition, many studies have reported that the activities of the digestive enzymes can be greatly down‐regulated in fish during fasting periods as a consequence of a reduction of mechanochemical stimulators of gastrointestinal tract (GI; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…liver (Barim-Öz, 2018;Bayir et al, 2011;Furné et al, 2009;Morales, Pérez-Jiménez, Carmen Hidalgo, Abellán, & Cardenete, 2004;Pascual, Pedrajas, Toribio, López-Barea, & Peinado, 2003; Pérez-Jiménez, Guedes, Morales, & Oliva-Teles, 2007). In addition, many studies have reported that the activities of the digestive enzymes can be greatly down-regulated in fish during fasting periods as a consequence of a reduction of mechanochemical stimulators of gastrointestinal tract (GI; e.g.…”
mentioning
confidence: 99%